Effect of high temperatures on the properties of lightweight geopolymer concrete based fly ash and glass powder mixtures - Turkey F.A.; Beddu S.B.; Ahmed A.N.; Al-Hubboubi S.K. (Elsevier Ltd, 2023)
Compressive strength; Concrete aggregates; Concrete mixtures; Gas emissions; Geopolymers; Glass; Greenhouse gases; Inorganic polymers; Light weight concrete; Microstructure; Water absorption; Energy; Expanded clay; Geopolymer concrete; Glass Powder; Greenhouse gas emissions; Highest temperature; Lightweight aggregates; Lightweight geopolymer; Powder mixtures; Property; Fly ash